Method for preparing medium-entropy micro-nano alloy by adopting refractory metal
The treatment of refractory metals and their alloys in the liquid phase by laser radiation method has solved the problem of insufficient density and uniformity of refractory metal alloys in the prior art, and a high-performance medium-entropy micro-nano alloy is prepared to avoid the introduction of impurities.
Patent Information
- Application Number
- CN202411985220.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the preparation of refractory metal alloys, the problems of large pores, uneven particle size distribution and difficulty in achieving complete densification and uniformity are often introduced in the preparation method of micro-nano medium entropy alloys, which affect the performance of the material.
By using laser radiation method, the refractory first metal and the second metal that are mutually soluble therewith are non-focused laser irradiated in the liquid phase to form alloy nanoparticles, and then laser irradiated in the liquid phase with the third metal to prepare a dense and uniformly distributed medium-entropy micro-nano alloy.
The density and uniformity of medium-entropy micro-nano alloys are achieved, the introduction of impurities such as surfactants is avoided, and the comprehensive performance of the material is improved.
Smart Images

Figure CN119772187A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of refractory metal alloys, and in particular to a method for preparing medium-entropy micro-nano alloys by using refractory metals. Background Art
[0002] Since refractory metal alloys are made by combining refractory metals with high melting points and strong corrosion resistance with medium-entropy alloys with low melting points, high electrical conductivity and thermal conductivity, and have the unique properties of both metals, they are widely used in the fields of sweat-generating materials, armor-piercing materials, and electrical contact materials. However, due to the large difference in the melting points of the two metals, poor wettability, and immiscibility, it is difficult to alloy the two metals.
[0003] The routes for preparing refractory metal alloys in the prior art are divided into vacuum infiltration method and liquid phase sintering method. Here, taking Cu-W alloy as an example, in vacuum infiltration, Ni-W alloy is prepared by pre-pressing and pre-sintering, and then the Ni-W alloy block material is infiltrated into molten liquid Cu, and then solidified to form a layered Cu-Ni-W alloy. The refractory alloy prepared by this method often has problems such as large pores and uneven particle size distribution. In liquid phase sintering, the elemental Cu, Ni and W powders are mixed, cold compressed, and then sintered at a temperature higher than the melting point of Cu. Due to the system immiscibility, poor wettability and large difference in melting temperature between W and Cu, it is difficult to achieve complete densification and sufficient uniformity of the Cu-W composite material prepared by this method, which is necessary to obtain an ideal high comprehensive performance alloy.
[0004] In addition, micro-nano medium-entropy alloys have a wide range of application prospects due to their unique microstructure and properties, such as 3D printing metal materials, high-temperature structural materials, thermal barrier coatings or thermoelectric materials. However, in some of the current physical or chemical methods for preparing micro-nano medium-entropy alloys, impurities such as surfactants are mostly introduced, which will affect the physical, chemical and mechanical properties of micro-nano alloys. For example, the impurity atoms will cause the lattice distortion of the alloyed micro-nano particles due to the difference in size or electronegativity between the impurity atoms and the matrix metal atoms; for another example, when the impurity atoms are insoluble in the micro-nano alloy, they will form an independent second phase or precipitate in the form of particles, resulting in changes in the microstructure of the micro-nano alloy, which in turn affects the performance of the entire micro-nano material. Summary of the invention
[0005] In view of the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a medium-entropy micro-nano alloy using a refractory metal. The present invention adopts a laser irradiation method, with a refractory first metal, a second metal that is mutually soluble in the refractory first metal, and a third metal that is immiscible with the refractory first metal but mutually soluble in the second metal as raw materials, firstly, the refractory first metal and the second metal are subjected to non-focused laser irradiation in a liquid phase, so that the two form alloy nanoparticles, and then the alloy nanoparticles and the third metal are subjected to non-focused laser irradiation in a liquid phase to obtain a medium-entropy micro-nano alloy. The medium-entropy micro-nano alloy obtained by the method of the present invention is dense and has a uniform distribution of components, and overcomes the technical defects of the prior art preparation method that introduces impurities such as surfactants.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a medium-entropy micro-nano alloy using a refractory metal comprises the following steps:
[0008] Nanoparticles of a refractory first metal and nanoparticles of a second metal that is mutually soluble therewith are mixed by ball milling, and then dispersed together in an organic solvent to obtain a mixed colloidal precursor solution.
[0009] The mixed colloidal precursor liquid is subjected to a first unfocused laser irradiation. During the first unfocused laser irradiation, the refractory first metal and the second metal have a strong absorption of the laser, while the organic solvent absorbs the laser very little. At this time, the refractory first metal and the second metal melt and evaporate, while the organic solvent hardly changes, thereby playing a role of rapid extraction and cooling to obtain an alloy colloidal solution. The solute in the alloy colloidal solution is alloy nanoparticles.
[0010] After ball milling, nanoparticles of the third metal are uniformly dispersed in an organic solvent to obtain a colloidal precursor solution of the third metal; wherein the third metal is immiscible with the refractory first metal but miscible with the second metal.
[0011] The alloy colloid solution is mixed with a colloid precursor solution of a third metal to obtain a nano-colloid solution.
[0012] The nano-colloidal solution is subjected to a second unfocused laser irradiation. During the second unfocused laser irradiation, the alloy nano-particles and the third metal have a strong absorption of the laser, while the organic solvent absorbs the laser very little. At this time, the alloy nano-particles and the third metal melt and evaporate, while the organic solvent hardly changes, which plays a role of rapid cooling to obtain a medium-entropy micro-nano alloy.
[0013] Preferably, according to the optimal thermodynamic alloying conditions of the alloy nanoparticles, the optimal thermodynamic conditions refer to the change in free energy, and free energy is a measure of the energy that a system can perform non-volume work under constant temperature and pressure conditions. By comparing the free energies of different phases at different molar ratios, it is determined which phases are stable phases at a given temperature and pressure. The stable phase is the state with the lowest free energy, and the molar ratio of the refractory first metal to the second metal is determined based on the stable phase.
[0014] Preferably, according to the optimal thermodynamic alloying conditions of the medium-entropy micro-nano alloy, by comparing the free energy of different phases at different molar ratios, it is determined which phases are stable phases at a given temperature and pressure. The stable phase is the state with the lowest free energy, and the molar ratio of the alloy nanoparticles to the third metal is determined based on the stable phase.
[0015] Preferably, the nanoparticles of the refractory first metal and the second metal that is miscible with the first metal are ball-milled to a consistent particle size, and the third metal is ball-milled to a consistent particle size with the alloy nanoparticles. Ball milling makes the particle size uniform, which is more conducive to uniform phase change, such as vaporization, after laser irradiation. In addition, ball milling can make different nanoparticles evenly mixed, which is conducive to increasing the laser alloying of the nanoparticles, rather than partially alloying and partially forming pure nanoparticles after laser irradiation.
[0016] Preferably, the refractory first metal is tungsten, rhenium, tantalum, molybdenum, niobium, iridium or vanadium.
[0017] Preferably, the second metal is nickel, iron, palladium or titanium.
[0018] Preferably, the third metal is silver or copper.
[0019] Preferably, the organic solvent is selected from one or more of ethanol, acetone, butanol and ethyl acetate.
[0020] Preferably, the conditions for the first unfocused laser irradiation are: using a 1064nm laser beam, a laser energy range of 350-500mJ, a temperature higher than the vaporization temperature of the nanoparticles of the refractory first metal and the second metal, and the conditions for the first unfocused laser irradiation are selected related to the absorption rate of the refractory first metal and the second metal, the organic solvent, and the laser interaction.
[0021] Preferably, the conditions for the second unfocused laser irradiation are: using a 1064nm laser beam, a laser energy range of 350-500mJ, and a temperature higher than the vaporization temperature of the alloy nanoparticles and the third metal. The selection of the conditions for the second unfocused laser irradiation is related to the absorption rate of the interaction between the alloy nanoparticles and the third metal, the organic solvent, and the laser.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention first irradiates the mutually soluble refractory first metal and second metal under the thermodynamic optimal alloying conditions, so that the two are vaporized at the same time, and under the rapid cooling effect of the liquid phase medium, uniformly dense alloy nanoparticles are formed, which are recorded as AB alloys; then the colloidal precursor liquid of the third metal is mixed with the alloy colloidal solution, and laser irradiated under the optimal thermodynamic alloying conditions to achieve the alloying of the refractory medium-entropy nano alloy. Under such conditions, the third metal can more easily replace part of the B atoms in the AB alloy, so that the prepared medium-entropy micro-nano alloy has better density and uniform size.
[0024] The present invention combines theory with experiment to prepare refractory metal medium-entropy micro-nano alloys in a liquid medium through a two-step method. Nanosecond pulse laser interacts with raw materials to generate high temperature and high pressure in the local area of nanoparticles, while the liquid medium is rapidly quenched and cooled, providing an excellent extreme environment for the preparation of refractory alloys. In the first step, an alloy of a refractory first metal and a second metal that is mutually soluble therewith is prepared, which not only improves the mutual solubility of the refractory first metal and the second metal, but also enhances the wettability with the third metal in the second step, greatly improving the compactness of the medium-entropy micro-nano alloy.
[0025] 2. The method of the present invention first obtains the thermodynamic conditions of metal alloys with large melting point differences through theoretical calculation. The large melting point difference refers to the refractory first metal and third metal, such as tungsten and copper, tungsten and silver. The large difference is due to the unique advantages of such alloys in the field of modern scientific and technological development. Such alloys can combine the respective advantages of the two metals. For example, tungsten-copper alloy combines the high hardness, low thermal expansion coefficient, high stability of tungsten with the excellent electrical conductivity and thermal conductivity of copper, and can be applied to the fields of electrical materials, anti-sweat materials, and armor-piercing materials; molybdenum-copper alloy has excellent high-temperature mechanical strength and low thermal expansion coefficient, and is widely used in the fields of electrical contact materials, sweating materials, and electronic packaging materials; tungsten-silver composite materials combine the excellent electrical conductivity and thermal conductivity of silver with the high melting point and high corrosion resistance of tungsten, and are used as electrical contact materials for medium and low voltage electrical switches.
[0026] Free energy is used to determine under what temperature, composition and particle size conditions, the micro-nano structure is more likely to form a two-phase structure or a single-phase structure. The single-phase free energy is lower than the two-phase free energy, and it is easier to form a single-phase solid solution, that is, an alloy, so as to find the composition, temperature or size that is most likely to form an alloy, and then use this simulation result to conduct experimental alloying, and use refractory metals to prepare medium-entropy micro-nano alloys, making alloying more controllable.
[0027] 3. The present invention adopts non-focused laser irradiation to prepare alloy nanoparticles and medium-entropy micro-nano alloys, and utilizes laser melting and evaporation to realize the preparation of refractory metal alloys. Moreover, during the preparation process, only by changing the laser flux, the controllable preparation of refractory metal alloys of different sizes can be achieved.
[0028] 4. The present invention selects parameters of non-focused laser irradiation, such as laser wavelength and laser flux, to achieve the simultaneous melting and evaporation phase transition of the refractory first metal and the second metal or the alloy nanoparticles and the third metal under specific laser parameters, thereby achieving controllable preparation of refractory metal alloys with uniform density.
[0029] 5. The method of preparing refractory metal alloys by non-focused laser irradiation in the present invention is simple and safe. There is no need to add auxiliary reagents, such as surfactants, and the alloying of micro-nano materials is directly carried out. Laser irradiation technology is used in a liquid medium to prepare medium-entropy micro-nano alloys with uniform density and controllable particle size through the discontinuity of time and space. The method is suitable for the alloying of a variety of refractory metals with different high melting points and low melting point metals, and the purity of the medium-entropy micro-nano alloys is improved.
[0030] 6. The reason why the present invention uses laser irradiation technology in a liquid medium to prepare a medium-entropy micro-nano alloy is that based on the interaction between the laser and the particles dispersed in the liquid medium, by adjusting the laser wavelength, energy density and other parameters, the controllable heating-melting-evaporation of the micro-nano material is achieved, thereby achieving the controllable preparation of ligand-free micro-nano materials. The existing technology only achieves the controllable preparation of metal, non-metal, metal / semiconductor micro-nano particles, while in this application, the laser irradiation technology is used to achieve the controllable preparation of medium-entropy micro-nano alloys with large melting point differences under extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the method for preparing medium-entropy micro-nano alloys using refractory metals in Example 1 of the present invention.
[0032] Figure 2 In the figure, (a) is a graph showing the relationship between the free energy of the nickel-tungsten alloy forming a two-phase structure and a single-phase structure and the particle size in Example 1 of the present invention, and (b) is a graph showing the relationship between the free energy of the nickel-tungsten alloy forming a two-phase structure and a single-phase structure and the tungsten component when the nickel-tungsten alloy particle size is 50nm.
[0033] Figure 3 In the figure, (a) is a relationship diagram between the free energy of the medium-entropy micro-nano alloy forming a two-phase structure and a single-phase structure and the particle size in Example 1 of the present invention, and (b) is a relationship diagram between the free energy of the medium-entropy micro-nano alloy forming a two-phase structure and a single-phase structure and the nickel-tungsten alloy when the size of the medium-entropy micro-nano alloy is 50nm.
[0034] Figure 4 This is the SEM image of the nickel-tungsten alloy of Example 1 of the present invention.
[0035] Figure 5 This is the SEM image of the copper-nickel-tungsten mesoentropy micro-nano alloy in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0037] The present invention provides a method for preparing a medium-entropy micro-nano alloy by using a refractory metal through laser irradiation, comprising:
[0038] The first step is to select a refractory first metal and a second metal that is miscible with it, calculate the optimal thermodynamic conditions for the two metals to form an alloy, and based on the simulation results, weigh nanoparticles of the refractory first metal and the second metal, mix them by ball milling, and then stir and evenly disperse them in an organic solvent to obtain a mixed colloidal precursor solution.
[0039] Among them, the selection of nanoparticles of the refractory first metal and the second metal is related to the mutual solubility between the nanoparticles. Mutual solubility is also called solubility or solid solubility, which refers to the maximum amount of one metal that can be dissolved in another metal, usually in mass percentage, atomic percentage or volume percentage under specific temperature and pressure conditions.
[0040] The mixed colloidal precursor liquid is irradiated with a modulated unfocused laser to obtain an alloy colloidal solution containing alloy nanoparticles. The selection of the unfocused laser is related to the absorption rate of the interaction between the refractory first metal and the second metal, the organic solvent, and the laser. Specifically, the refractory first metal and the second metal have strong absorption of the laser, while the organic solvent has little absorption of the laser. The purpose is to melt and evaporate the refractory first metal and the second metal, while the organic solvent hardly changes, thereby achieving a rapid cooling effect.
[0041] The second step is to select a third metal that is immiscible with the refractory first metal but miscible with the second metal, ball-mill the third metal, and evenly disperse it in an organic solvent to obtain a colloidal precursor solution of the third metal.
[0042] The optimal thermodynamic conditions for the alloy nanoparticles and the medium-entropy micro-nano alloys that can be formed with the third metal are calculated. Based on the simulation results, the alloy colloidal solution is mixed with the colloidal precursor solution of the third metal to obtain a nano-colloidal solution.
[0043] After the nano-colloid solution is irradiated with laser, it is dried to finally obtain a medium-entropy micro-nano alloy containing the first, second and third metal elements.
[0044] In summary, the present invention provides a method for preparing medium-entropy micro-nano alloys using refractory metals as raw materials and laser irradiation methods. The refractory metal alloy can be prepared simply and efficiently using a two-step method. The first step is to use theoretical calculations of the thermodynamic conditions under which nanoparticles of a refractory first metal and a second metal that is mutually soluble therewith can form an alloy, and under the photothermal effect of lasers and nanoparticles, the refractory first metal and the second metal form alloy nanoparticles in a liquid medium; the second step is to use theoretical calculations of the thermodynamic conditions under which alloy nanoparticles and a third metal can form an alloy, and then laser irradiate them again after mixing, so that each metal particle quickly melts and alloys, and condenses, nucleates and grows under the ultrafast quenching mechanism of the liquid medium, guiding the rapid synthesis of the refractory alloy from a kinetic scale.
[0045] Adding the second metal that is miscible with the refractory first metal in the first step will increase the interfacial bonding strength between the refractory first metal and the immiscible third metal, relieve stress concentration at the interfacial interface, and thus enhance the solubility of the alloy nanoparticles and the third metal in the second step.
[0046] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the present invention is described in detail with reference to specific embodiments below.
[0047] Example 1
[0048] A method for preparing a medium-entropy micro-nano alloy using a refractory metal comprises the following steps:
[0049] (1) Preparation of nickel-tungsten mixed colloidal precursor solution: According to theoretical calculation results, 2.5 mg of nickel powder and tungsten powder with a molar ratio of 7:3 were weighed, ball-milled and stirred for 20 min, and then placed in 5 mL of organic liquid medium ethanol. After sufficient stirring, a 0.5 mg / mL nickel-tungsten mixed colloidal precursor solution was obtained.
[0050] (2) Preparation of nickel-tungsten alloy colloidal solution by laser irradiation: The wavelength was 1064 nm and the energy density was 500 mJ / pulse*cm 2 The nickel-tungsten mixed colloidal precursor solution is irradiated with an unfocused laser for 5 minutes. Stirring is continued during the irradiation process to obtain a nickel-tungsten alloy colloidal solution. The solute in the nickel-tungsten alloy colloidal solution is nickel-tungsten alloy.
[0051] (3) Preparation of a copper colloidal precursor solution: Weigh 2.5 mg of copper nanopowder, stir it by ball milling for 20 min, and place it in 5 mL of organic liquid medium ethanol. After sufficient stirring, a 0.5 mg / mL copper colloidal precursor solution is obtained.
[0052] (4) Preparation of nano-colloidal solution: According to theoretical calculation results, the nickel-tungsten alloy colloidal solution and the copper colloidal precursor solution are uniformly mixed in a liquid medium, and the molar ratio of the nickel-tungsten alloy to the copper is 5:5, to obtain a 0.5 mg / mL nano-colloidal solution.
[0053] (5) Preparation of copper-nickel-tungsten alloy powder by laser irradiation: The wavelength is 1064 nm and the energy density is 500 mJ / pulse*cm 2 The nano-colloidal solution was irradiated with an unfocused laser for 5 minutes with continuous stirring during the irradiation process. Finally, after drying and other treatments, the copper-nickel-tungsten medium-entropy micro-nano alloy was obtained.
[0054] The following study is conducted by taking the copper-nickel-tungsten medium-entropy micro-nano alloy obtained in Example 1 as an example, and the specific research method and results are as follows:
[0055] like Figure 1 As shown, the technical solution of the present invention is universal in the preparation of medium-entropy micro-nano alloys.
[0056] Figure 2 is a thermodynamic free energy calculation diagram of the refractory metal tungsten and the metal nickel miscible therewith in Example 1, Figure 2 (a) shows the relationship between the free energy and particle size of the two-phase structure and the single-phase structure when the nickel-tungsten molar ratio is 7:3. Under this ratio, the free energy of the single-phase structure is lower than the free energy of the two-phase structure when the particle size of the nickel-tungsten alloy ranges from a few nanometers to 200 nanometers, so the formation of the micro-nano structure is more inclined to the single-phase solid solution structure. Figure 2 In (b), when the nickel-tungsten alloy particle size is 50nm, the relationship between the free energy of forming a two-phase structure and a single-phase structure and the tungsten component. At this particle size, the free energy of forming a single-phase solid solution of micro-nano particles of different components is less than the free energy of a two-phase structure, and when the nickel-tungsten molar ratio is 7:3, the free energy of forming a single phase is the lowest, which is the optimal component ratio for forming the alloy. And the free energy difference is the largest when the nickel-tungsten molar ratio is 7:3.
[0057] Figure 3 (a) shows the relationship between the free energy and particle size of the two-phase structure and the single-phase structure formed by alloying nickel and tungsten at a molar ratio of 7:3 and then mixing with copper at a molar ratio of 5:5. Under this ratio, the free energy of the medium-entropy micro-nano alloy particles ranging from a few nanometers to 200 nanometers is lower than the free energy of the two-phase structure, and is more inclined to the single-phase solid solution structure. Figure 3(b) shows the relationship between the free energy of forming two-phase structure and single-phase structure and the composition after alloying nickel and tungsten at a molar ratio of 7:3 when the medium entropy micro-nano alloy particle size is 50nm. At this particle size, the free energy of forming a single-phase solid solution of medium entropy micro-nano alloy particles with different compositions is less than the free energy of the two-phase structure, and when the molar ratio is 5:5, the free energy of forming a single phase is the lowest, which is the optimal composition ratio for forming an alloy.
[0058] Figure 4 The scanning electron microscope image of the nickel-tungsten alloy prepared in Example 1 is shown in FIG. Figure 4 It can be obtained that the particle size of the nickel-tungsten alloy nanoparticles is several hundred nanometers. The corresponding energy spectrum distribution results in Table 1 show that these nanoparticles still contain NiW elements, indicating that the nickel powder and tungsten powder are decomposed / separated during the photothermal process and maintain their original properties.
[0059] Table 1 EDS data of nickel-tungsten alloy
[0060] element Mass% Mass percentage error % Atomic percentage % Atomic Percent Error % Ni 71.21 ±0.46 88.57 ±0.25 W 28.79 ±1.88 11.43 ±0.33 total 100 100
[0061] Figure 5 is a scanning electron microscope image of the medium entropy micro-nano alloy of Example 1, Figure 5 It can be obtained that the particle size of the nanoparticles is several hundred nanometers. The corresponding energy spectrum distribution results in Table 2 show that these nanoparticles still contain CuNiW elements, indicating that the nickel-tungsten alloy and copper powder undergo decomposition / separation during the photothermal process and maintain their original properties.
[0062] Table 2 EDS data of copper-nickel-tungsten medium-entropy micro-nano alloy
[0063] element Mass% Mass percentage error % Atomic percentage % Atomic Percent Error % Ni 24.78 ±0.52 27.51 ±0.51 Cu 68.51 ±0.89 70.25 ±0.82 W 6.71 ±0.44 2.24 ±0.14 total 100 100
[0064] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing medium-entropy micro-nano alloys using refractory metals, characterized in that: The steps include: Mixing nanoparticles of a refractory first metal and nanoparticles of a second metal that is mutually soluble therewith, and then dispersing them together in an organic solvent to obtain a mixed colloidal precursor solution; The mixed colloidal precursor solution is subjected to a first non-focused laser irradiation to obtain an alloy colloidal solution, wherein the solute in the alloy colloidal solution is alloy nanoparticles; uniformly dispersing nanoparticles of a third metal in an organic solvent to obtain a colloidal precursor solution of the third metal; wherein the third metal is immiscible with the refractory first metal but is miscible with the second metal; mixing the alloy colloidal solution with a colloidal precursor solution of a third metal to obtain a nano-colloidal solution; The nano-colloidal solution is subjected to a second unfocused laser irradiation to obtain a medium-entropy micro-nano alloy.
2. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The molar ratio of the refractory first metal to the second metal is determined according to the optimal thermodynamic alloying conditions of the alloy nanoparticles.
3. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The molar ratio of the alloy nanoparticles to the third metal is determined according to the optimal thermodynamic alloying conditions of the medium-entropy micro-nano alloy.
4. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The nanoparticles of the refractory first metal and the second metal that is mutually soluble therewith are ball-milled to have the same particle size, and the third metal is ball-milled to have the same particle size as the alloy nanoparticles.
5. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The refractory first metal is tungsten, rhenium, tantalum, molybdenum, niobium, iridium or vanadium.
6. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The second metal is nickel, iron, palladium or titanium.
7. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The third metal is silver or copper.
8. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The organic solvent is selected from one or more of ethanol, acetone, butanol and ethyl acetate.
9. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The conditions of the first unfocused laser irradiation are: using a 1064 nm laser beam, a laser energy range of 350-500 mJ, and a temperature higher than the vaporization temperature of the nanoparticles of the refractory first metal and the second metal.
10. The method for preparing medium-entropy micro-nano alloys using refractory metals according to claim 1, characterized in that: The conditions of the second unfocused laser irradiation are: using a 1064 nm laser beam, a laser energy range of 350-500 mJ, and a temperature higher than the vaporization temperature of the alloy nanoparticles and the third metal.
Citation Information
Patent Citations
Device of preparing metal nanometer particle colloid by liquid phase medium pulse laser ablation
CN100999019A
Nanoparticles are generated in liquids by ablation with high-repetition-rate ultrashort pulse lasers.
CN102292159A
Method for preparing solid-dissolved high-bactericidal-activity nanometer Ag-Cu alloy powder by means of in-liquid pulse energy technology
CN105689727A
Device for continuously preparing nanoparticles by using liquid-phase laser ablation method
CN115283684A
Method for preparing high-entropy alloy through organic liquid phase laser irradiation at normal temperature and pressure
CN117403093A